Late to post-Variscan basement segmentation and differential exhumation along the SW Bohemian Massif, central Europe - Eberts, Andreas; Fazlikhani, Hamed; Bauer, Wolfgang; Stollhofen, Harald; de Wall, Helga; Gabriel, Gerald (Solid Earth, 2021)
The exposed Variscan basement in central Europe is well-known for its complex structural and lithological architecture resulting from multiple deformation phases. We studied the southwestern margin of the Bohemian Massif, which is characterized by major and long-lived shear zones, such as the Pfahl and Danube shear zones, extending over >ĝ€¯100ĝ€¯km and initiated during Variscan tectonics. We integrated Bouguer gravity anomaly and lidar topographic data analyses and combined our results with available data and observations from low-Temperature thermochronology, metamorphic grades, and the exposed granite inventory to detect patterns of basement block segmentation and differential exhumation. Three NW-SE-striking basement blocks are bordered by the Runding, Pfahl, and Danube shear zones from the northeast to the southwest. Basement block boundaries are indicated by abrupt changes in measured gravity patterns and metamorphic grades. By applying high-pass filters to gravity data in combination with lineament analysis, we identified a new NNW-SSE-striking tectonic structure (Cham Fault), which further segments known basement blocks. Basement blocks that are segmented by the Cham Fault differ in the abundance and spatial distribution of exposed late Variscan granites and are further characterized by variations in apparent thermochronological age data. Based on our observations and analyses, a differential exhumation and tectonic tilt model is proposed to explain the juxtaposition of different crustal levels. Block segmentation along the NW-SE-striking Pfahl and Runding shear zones most likely occurred prior, during, and after late orogenic granite emplacement at ca. 320ĝ€¯±ĝ€¯10ĝ€¯Ma, as some of the granites are cross-cut by the shear zones, while others utilized these structures during magma ascent and emplacement. In contrast, activity and block segmentation along the Cham Fault occurred after granite emplacement as the fault sharply truncates the granite inventory. Our study provides evidence of intense and continuous fault activities during late and post-orogenic times and highlights the importance of tectonic structures in the exhumation and juxtaposition of different crustal levels and the creation of complex lithological patterns in orogenic terrains.
CRIS-Team Scopus Importer:2021-10-29

Morphotectonic analysis of basement and cover units in eastern Bavaria, SE Germany - insights into the deeper crustal architecture? - Eberts, Andreas; Schaarschmidt, Anna; Bauer, Wolfgang; Stollhofen, Harald; de Wall, Helga (GeoBonn 2018, 2018)
The topographic expression of landscapes directly depends on the interaction between exposed rock type, erosion and tectonic deformation. In areas where high rates of active deformation pre-vail, the effects of faulting and folding are often immediately transferred to the Earth’s surface. By contrast, in areas where ongoing, rapid deformation is absent, as it is assumed for large parts of eastern Bavaria, erosional processes need to utilize gradients in erodibility to uncover already existent tectonic structures. In that case, resulting topographic features are not visible as well-defined fault scarps but as linear to curvilinear river valleys, ridgelines or slope breaks. Because these lineaments outline structures that formed during ancient tectonic events, mapping of them yields important information about the general structural framework of the subsurface. Here, we present results from an integrated study, using high-resolution digital elevation models from airborne LiDAR surveys combined with gravity data to reveal the morphotectonic feature inventory of eastern Bavaria, SE Germany, and its relation to the underlying crustal architecture. The studied area comprises the western border zone of the Bohemian Massif, a region well known for hosting some of the largest fault zones existing in Central Europe, such as the Pfahl Fault Zone (PFZ) and Danube Fault Zone (DFZ). Post-Variscan to Alpine reactivation of earlier struc-tures led to a complex structural pattern along these faults and ultimately resulted in the uplifted and exposed basement complex of the Bohemian Massif. Our results show that the investigated area is segmented into several domains of different orders. 1st order domains, best delineated in gravity data, are thought to represent large crustal blocks which partly root into the upper mantle. These are assigned to the Saxothuringian, Teplá-Barran-dian and Moldanubian crustal units. In contrast, 2nd order domains additionally show distinct var-iations in the arrangement of topographic lineaments and in other DEM-specific parameters such as surface roughness indices and altitude distributions. In the Bavarian Forest, for example, a central domain of high gravity is also characterized by predominantly N-S oriented lineaments and an increased surface roughness. Furthermore, 2nd order domains are separated by large topographic lineaments, some of which situated in close vicinity to already known fault zones such as the PFZ and DFZ. However, our study also identifies previously unknown locations of ancient fault zones, ultimately indicating an even more complex structural evolution and crustal architecture of eastern Bavaria and the western border zone of the Bohemian Massif.<br

Tectonic impact on sediment routing systems of evolving rift basins: A case study from the Cenozoic Kerimbas Graben, offshore northern Mozambique - Eberts, Andreas; Kaufmann, Dirk; Stollhofen, Harald; Franke, Dieter (17th Symposium of Tectonics, Structural Geology and Crystalline Geology (TSK), 2018)
Knowledge of the submarine channel architecture and of related tectonosedimentary processes is crucial to assess sediment influx and to locate potential hydrocarbon reservoirs. Such systems are highly sensitive to changes of seabed topography, often strongly linked to tectonic uplift, faulting and seismicity. To reveal the impact of tectonic activity on channel pathways, we carried out a morphotectonic analysis of the Kerimbas Graben, an active rift basin situated in the Mozambique Channel. This area is highly influenced by the Cenozoic to recent tectonic evolution of the East African Rift System. Three high-quality geophysical datasets including high-resolution bathymetric, multichannel reflection seismic and Parasound data were acquired during two cruises of the research vessel SONNE in early 2014. By combining these datasets, we were able to map the lateral and vertical extent of topographic features such as fault scarps and channel incisions, and to interpret them in terms of their relation to tectonic activity. Our results show that the study area is divided into two distinct parts, comprising differences in both morphotectonic characteristics and in the evolution of channel pathways. The northern part, occupied by the Kerimbas Graben, shows N-S trending fault scarps the most pronounced of which are associated with the eastern and western border faults of the rift basin. Farther south, an area of “diffuse extension” is accompanied by horst-and-graben structures, acting as right-stepping transfer zones for the southward impinging eastern border fault. The observed spatial variations are also represented by differences in fault throw, revealing that fault scarps in the southern part of the study area show significantly lower vertical offsets. By assuming a roughly coherent age of the corresponding faults this suggests higher uplift rates in the Kerimbas Graben area, which in turn would imply differences in the impact of tectonics on sediment routing systems along strike of the rift. Concerning this, two basic types of interactions in the downstream parts of submarine channel systems can be inferred: (1) a complete blocking of the channel pathway occurred in areas where the rate of rift shoulder uplift exceeded the rate of channel incision. Uplifted channel remnants on the eastern rift flank of the Kerimbas Graben are indicative for this process. Since they were formed at least during the Late Miocene, they confirm Cenozoic tectonics to be responsible for the formation of the rift basin; (2) In contrast, active incision into the rift shoulder occurred in areas where the uplift rate of the shoulder is substantially lower than the downward erosion of the channel system. This is most likely the case for the southern part of the study area where a channel has incised deeply into the eastern rift shoulder. Based on these results, we established an evolutionary model for the interaction of tectonic activity and sediment routing systems of the Kerimbas Graben and adjacent southern areas, ranging from the Late Miocene to recent time

The Evolution of Central Volcanoes in Ultraslow Rift Systems: Constraints From D. João de Castro Seamount, Azores - Romer, René; Beier, C.; Haase, Karsten; Eberts, Andreas; Hübscher, C. (Tectonics, 2021)
The Dom João de Castro seamount in the Hirondelle Basin (Azores) is a central volcano on the ultraslow diverging Terceira Rift axis. The combination of structural and geochemical data provides insights into the evolution of central volcanoes in oceanic rift systems above the Azores melting anomaly. The orientation of fault scarps and volcanic structures at D. João de Castro and the adjacent Castro fissure zone indicate that the regional SW-NE extending stress field dominates the morphology of the NW Hirondelle Basin. The regional tectonic stress field controls the crustal melt pathways and leads to dike emplacement along fissure zones and the prevalent eruption of mafic lavas. The occurrence of mafic to felsic lavas at D. João de Castro gives evidence for both a deep and a shallow crustal melt reservoir generating a subordinate local stress field at the seamount. New Sr-Nd-Pb isotope data along with incompatible trace element ratios indicate that D. João de Castro and the Castro Ridges originated from similarly heterogeneous mantle source but did not form simultaneously. Our new model implies that central volcanoes along the Terceira Rift form by the growth of volcanic ridges and transitioned into circular edifices after magmatic systems generate local changes in the regional lithospheric stress field. The geometry of D. João de Castro and other magmatic systems along the Terceira Rift combined with the alkaline nature of the erupted lavas, and the large lithosphere thickness indicates that young oceanic rifts are more similar to continental rifts rather than mid-ocean ridges.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Azores; central volcano; intraplate volcanism; melt transport; rifting; Terceira Rift